Use of a bibliometric literature review to assess medical research capacity in post‐conflict and developing countries: Somaliland 1991–2013. Issue 11 (14th September 2015) - Boyce, Ross; Rosch, Richard; Finlayson, Alexander; Handuleh, Djibril; Walhad, Said Ahmed; Whitwell, Susannah; Leather, Andy
Abstract Objectives Effective healthcare systems require high‐quality research to guide evidence‐based interventions and strategic planning. In low‐ and middle‐income countries, especially those emerging from violent conflict, research capacity often lags behind other aspects of health system development. Here, we sought to bibliometrically review health‐related research output in Somaliland, a post‐conflict self‐declared, autonomous nation on the Horn of Africa, as a means of assessing research capacity. Methods We reviewed articles on health‐related research conducted in Somaliland between 1991 and 2013 that included a description of the experimental design, and articles were published in either a peer‐reviewed journal or as part of a scholarly programme receiving formal review. We did not include policy or social science research that did not enrol or interact with subjects from Somaliland. Using online databases, all studies meeting minimum eligibility criteria were reviewed in regard to Somaliland‐based co‐authorship, topic of research and specific measures of quality. Results A total of 37 studies were included in this review. Of these, only 19 (51%) included co‐authorship by Somaliland‐based researchers. Of the 21 studies reporting ethical approval, 16 (64%) received approval from the Somalia or Somaliland Ministry of Health, while five received approval from a university or national commission. More than two‐thirds of published research was limited to a few areas of investigation with most (19, 51%) following basic cross‐sectional study designs. The number of articles published per year increased from 0 to 1 in the years 1991–2007 to a maximum of 8 in 2013. Conclusions Research activity in Somaliland is extremely limited. Investigators from high‐income countries have largely directed the research agenda in Somaliland; only half of the included studies list co‐authors from institutions in Somaliland. Leadership and governance of health research in Somaliland is required to define national priorities, promote scholarly activity and guide the responsible conduct of research. The methods used here to assess research capacity may be generalisable to other low‐ and middle‐income countries and post‐conflict settings to measure the impact of research capacity‐building efforts.